Recognising entailment on fast food and snack utterances in YouTube commercials (Passage: Journal of English Language and Literature, 2025)
This study examines the use of entailment in fast food and snack commercials on YouTube, with the aim of identifying and comprehending the types of entailment present, as well as determining the most dominant type employed. A qualitative descriptive method was adopted, and content analysis was used to examine selected commercials. Utterances from these commercials were transcribed and analyzed to identify patterns of entailment. The data were collected through purposive sampling, focusing specifically on fast food and snack commercials that demonstrated entailment features in their language. The findings reveal the presence of two types of entailments: one-way entailment and two-way entailment. Of the 13 utterances identified, 11 were categorized as one-way entailment, in which the truth of one proposition implies the truth of another. The remaining two utterances demonstrated two-way entailment, where both statements mutually imply each other and express equivalent meanings in different forms. The findings indicate that one-way entailment is the most dominant type used in the sampled commercials. The study offers insights into how entailment functions as a linguistic feature to reinforce key messages in the commercials, providing a foundation for further research on semantic strategies in media discourse.